2015
DOI: 10.4081/ejh.2015.2570
|View full text |Cite
|
Sign up to set email alerts
|

High temperature requirement A1, transforming growth factor beta1, phosphoSmad2 and Ki67 in eutopic and ectopic endometrium of women with endometriosis

Abstract: Increasing evidence supports the hypothesis that TGFβ1 signalling may be mediated by high temperature requirement A1 (HtrA1) serine protease, acting on important regulatory mechanisms such as cell proliferation and mobility. Evidence is now accumulating to suggest that HtrA1 is involved in the development and progression of several pathologies. The aim of this study was to evaluate: i) if HtrA1 and TGFβ1 expressions differ in eutopic and ectopic endometrium in women with endometriosis; ii) if HtrA1 correlates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 41 publications
0
19
2
Order By: Relevance
“…According to the widely accepted theory of retrograde menstruation, the endometrium is the source of ectopic endometriotic foci. Previous studies showed that the eutopic endometrium contributed to the pathogenesis of endometriosis due to the increase of proliferation, migration and invasion of ectopic endometrium [29][30][31][32][33]. In this study, we did not detect a significant difference in patients' uric acid level in serum.…”
Section: Discussioncontrasting
confidence: 80%
“…According to the widely accepted theory of retrograde menstruation, the endometrium is the source of ectopic endometriotic foci. Previous studies showed that the eutopic endometrium contributed to the pathogenesis of endometriosis due to the increase of proliferation, migration and invasion of ectopic endometrium [29][30][31][32][33]. In this study, we did not detect a significant difference in patients' uric acid level in serum.…”
Section: Discussioncontrasting
confidence: 80%
“…The protein expression levels of TGFB1 and SMAD3 between eutopic and normal endometrium groups differed insignificantly, which is inconsistent with previous studies (Johnson et al 2005, Cruz et al 2015. Another research reported that only weak upregulation of TGFB1 in endometriosis eutopic endometrium occurred compared with the controls (Goteri et al 2015). The present study is the first to compare the protein expression levels of TGFB1 and Figure 7 (A) Representative photomicrographs of macrophages with and without co-culturing (original magnification, ×400).…”
Section: Discussioncontrasting
confidence: 91%
“…Retinol dehydrogenase 10 (RDH10) is a key enzyme for vitamin A metabolism and is essential for embryonic patterning, morphogenesis and survival [30]. In addition, TGF-β1 (transforming growth factor-beta 1) is abundantly expressed in the endometrium and secreted into the uterine fluid to regulate uterine function [31]. Growth and differentiation factor 9 (GDF9) is secreted by oocytes and plays a leading role in the control of ovarian function in reproduction [32].…”
Section: Discussionmentioning
confidence: 99%